Sources, biosynthesis, and analytical methods of foodborne biogenic amines - Nurul Fatihah, Masdar; Muhammad Abdurrahman, Munir; Nor Hisam, Zamakshshari; Sim Siong, Fong (Elsevier B.V., 2026)
An excessive number of biogenic amines can lead to food poisoning. Ensuring proper food safety evaluation is essential to control this risk. Research has been conducted on the synthesis of biogenic amines, extraction methods, detection techniques, and pharmacological effects. However, there is a lack of comprehensive evaluations that encompass all these elements. Notable gaps remain in the toxic effects of various BAs, and their interactions with food have not been thoroughly investigated. This review aims to provide an assessment of the sources, synthesis pathways, extraction techniques, and detection developments of biogenic amines, as well as their toxicological consequences in foods. Focus is devoted to the relationship between the synthesis pathways of biogenic amines and their occurrence levels in food matrices, as well as the relationship between extraction and detection methods and their impact on safety evaluation. The results of this compilation indicate that the evaluation of biogenic amine occurrence and their toxic effects in food have notably improved food safety evaluation. Based on these findings, it is recommended that the understanding of biogenic amines in food be enhanced and that the urgent necessity for ongoing innovation and methodological improvement be highlighted. This work is significant as it assesses the relationship between biogenic amines and safety evaluation, thereby supporting compliance with food safety regulations and reducing health hazards associated with biogenic amine exposure.